Beasiswa Negara, Identitas Nasional dan Ketidaknyamanan Moral Perspektif Politik Pendidikan atas Kasus Dwi Sasetyaningtyas - Ahmad Zaky Mubarok; Arifa Halwa Khairunnisa; Arnis Desgita Eka Putri; Aulia Putri Maharani; Gladis Kartika Dewi; Nabila Putri Sammanda; Nasywa Nurul Aini; Zelfanya Rahmayantri; Abdul Ghofur (Penerbit Jurnal Indonesia, 2026)
This study examines the role of state scholarship programs, particularly LPDP, as instruments of educational politics that not only expand access to higher education but also shape national identity and moral expectations. Employing a critical qualitative approach and a case study of Dwi Sasetyaningtyas (2026), the research investigates the tension between fulfilling administrative requirements and responding to evolving public moral demands. The analysis is grounded in Antonio Gramsci's concept of hegemony and Willem Schinkel's theory of moral citizenship. The findings indicate that state scholarships establish a